Higher levels of circulating TIMP-4 in preeclampsia is strongly associated with clinical parameters and microRNA - Sandrim, Valéria C. [UNESP]; Diniz, Solange; Eleuterio, Nibia Mariana; Gomes, Karina B.; Dusse, Luci Maria S.; Cavalli, Ricardo C. (Taylor & Francis, 2018)
Background: Preeclampsia results in maternal and fetal complications and some studies have reported the role of MMPs and TIMPs in its pathophysiology. Therefore, the aim of this study was to compare plasma TIMP-4 levels in preeclampsia and healthy pregnant; and to correlate these levels with clinical parameters and expression of Let7a-5p (3´UTR post-transcriptionally regulation) Methods: TIMP-4 was measured by ELISA and miR-Let7a-5p expression by qPCR. Results: Elevated plasma TIMP-4 levels in preeclampsia compared to healthy pregnant was found 1450 ± 411 vs. 775 ± 210 pg/mL, respectively (p < 0.0001); these levels are correlated positively with serum liver enzymes (ALT, r = 0.84, p = 0.004; and AST, r = 0.51, p = 0.02); and negatively with newborn weight (r = −0.45, p = 0.04) in preeclampsia. Regarding Let7a-5p a negative but not significant correlation was found (r = −0.39, p = 0.06, including both healthy and preeclampsia). Conclusions: Preeclampsia present elevated levels of circulating TIMP-4 compared to healthy pregnant and these levels are correlated with clinical parameters of disease.
Keywords: Let-7a-5p; microRNA; MMPs; Preeclampsia; TIMP-4; TIMPs